Pengaruh Kecepatan Udara Terhadap Performa Crossdraft Gasifier Dengan Bahan Bakar Sekam Padi - Ma'rup, Nurhasan, Nur aklis, ST, M.Eng, Sartono Putro, Ir, MT (2015)
Fossil fuels including fuel is exhaustible (non-renewable). Total consumption of fossil fuels either petroleum, natural gas, or coal in Indonesia is increasing year. Rice husk biomass is a renewable energy and great potential in Indonesia. Through gasification, burned rice husk with limited oxygen to produce syngas that is susceptible to burn. This study aims to determine the effect of air speed variation of the temperature of combustion, the temperature of boiling water, effective flame and thermal efficiency of the furnace. In this study begins by modifying the airways in the reactor, then the supply of air from the blower to vary the speed, the size of the reactor diameter of 170 mm. Air speed used was 4.5 m / s, 5.5 m / s and 6.5 m / s, then measured the temperature of combustion and the temperature of boiling water every 0.5 minutes. The results showed variations in airspeed affects the combustion temperature, the temperature of boiling water, effective flame and furnace thermal efficiencies generated. Air velocity 4.5 m / s for 870.67C highest combustion temperature, the temperature of boiling water for 3.5 minutes, effective flame for 15 minutes and at 5.64% furnace efficiency. Air velocity 5.5 m / s for 878.67C highest combustion temperature, the temperature of boiling water for 3 minutes, the flame effective for 12.5 minutes and the efficiency of the furnace at 6.19%. Air velocity of 6.5 m / s for 933.33C highest combustion temperature, the temperature of boiling water for 2.5 minutes, effective flame for 10 minutes and at 6.36% furnace efficiency. Keywords: Gasification, rice husks, airspeed, crossdraft gasifier